Menjadi Gereja yang Miskin untuk Orang Miskin: Relevansi Mater Et Magistra di Paroki Ratu Rosari Fatima Kesatrian - Martina Minaratih; Teresia Noiman Derung (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2024)
This research explores the implementation of Mater et Magistra values ​​in the local context of Ratu Rosari Fatima Kesatrian Parish, with a focus on the role of the Church as an agent of social and spiritual transformation. This approach is realized through diakonia services, community empowerment programs, and priority management that avoids consumerism. The Church combines liturgy with real action to address the challenges of poverty and injustice in its community, in line with the call to be a "poor Church for the poor." The research results show that this solidarity-based approach not only strengthens the relevance of the Church, but also has a significant impact in empowering congregations and local communities. This research recommends expanding empowerment programs, collaboration with communities, and regular evaluation for the sustainability of the Church's mission in serving the poor.